The Potential of Allergen Biochips - Wohrl, Stefan (Recent Patents on Inflammation & Allergy Drug Discovery, 2008)
Immediate-type allergies (type I) allergies to environmental allergens such as plant pollen, pet dander, food, honeybees' and wasps' venom affect around a third of the total population in developed countries. The diseases comprise a broad spectrum from rather mild diseases such as hay fever and skin reactions like urticaria to severe ones such as bronchial asthma, vomiting and diarrhea and finally anaphylactic shock. Type I allergies are caused by an errant immune response leading to the production of allergen-specific IgE. The usual algorithm for the diagnosis of type I allergies begins with obtaining a detailed patient history and continues with the confirmation by skin tests and/or in vitro measurement of IgE. Allergen biochips are a promising new technology for the in vitro measurement of specific IgE in type-I allergic patients. In contrast to conventional in vitro tools, they consist of multiple allergen components spotted onto a microarray. This allows to perform multiple analyses in a single measurement analysing patient-specific sensitisation patterns, the so called “component resolved diagnosis&rdquo. This review considers prospects and difficulties with this new technology and also reviews patents related to this field.
Keywords: diagnosis of allergy